(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2019)
An alternative transliteration of Russian letters in Latin is proposed, including only four digraphs, which differs favorably from previous ones in using all 26 letters of the Latin alphabet (plus an apostrophe) and in lacking diacritical marks above the letters and allows the Russian text of any complexity to be transmitted in Latin letters (and vice versa) with the maximum simplicity extremely unambiguous.